Yarıiletken Polimerlerden Hazırlanan İnce Filmlerin Elektriksel Ve Spektroskopik Özelliklerinin İncelenmesi ve Organik Güneş Hücreleri - Aktuna, Mehmet Selim (Fen Bilimleri Enstitüsü, 2016)
Bu tez çalışmasının başlıca amaçları, organik yarıiletken olan P3HT’nin değişik miktardaki kamfor sülfonik asit ile katkılandırarak ve değişik tavlama sıcaklıklarındaki, spektroskopik ve elektriksel özelliklerinin belirlenmesi ayrıca katkılandırılmış organik yarıiletkenler ile verimliliği arttırılmış organik güneş hücrelerinin elde edilmesidir. P3HT organik yarıiletkenine ek olarak,  PCDTBT organik yarıiletkeni de kullanılarak elde edilen ince filmlerin elektiriksel ve spektroskopik özelliklerinin belirlenmesidir. Son olarakta, PCPDTBT ile yapılan organik güneş hücrelerinin karakterize edilmesidir. P3HT ile yapılan çalışmalarda kamfor sülfonik asit ile katkılandırarak, P3HT ince filmlerinin iletkenliği arttırlmıştır. Fakat soğrulma spekturumunda verdiği geniş pikin, kızılaltı bölgeye doğru kayması gözlenmemiştir. Ama PCPDTBT ile yapılan çalışmalarda DBSA katkısı ile soğrulmanın kızılatı bölgeyi de kapsayacak şekilde olduğu görülmüştür.  Organik güneş hücrelerinin en büyük avantajı düşük maliyetli ve esnek bir şekilde üretiminin mümkün olmasıdır. Yani esnek güneş hücreleri üretilebilir.  Dünya üzerinde enerji ihtiyacı gün geçtikçe artmaktadır ve bu enerji olmadan örneğin, suyu saflaştıramayız ya da bilgisayarlarımızı kullanamayız. Dünya üzerinde şuan ki enerji ihtiyacı yaklaşık olarak  18 TW (18×1012 Watt)’dır ve artan dünya nüfusu ile, bu ihtiyaç gittikçe artmaktadır. Ayrıca bu ihtiyacın çoğu fosil yakıtlardan karşılanmakta ve buna paralel olarak karbondioksit salınımı artarak çevreye zarar vermektedir. Bu sebepten dolayı yenilenebilir enerji kaynaklarına olan ihtiyaç gün geçtikçe artmaktadır. Bu yenilenebilir enerji kaynaklarından en güvenilir ve çevre dostu olanı güneş enerjisidir. Her gün dünyaya yaklaşık olarak 1.2×105 TW enerji gelmektedir yani güneşten gelen bu enerji, şuan ki tüketilen enerjiden çok daha fazladır. Bu enerjiyi kullanabilmek için ise,  güneş hücreleri kullanmamız gerekir. Böylece, güneş hücreleri ile güneşten gelen ışık enerjisini elektrik enerjisine çevirmek mümkündür. Bu sebeplerden dolayı bu tez çalışmasında organik güneş hücrelerinin verimliliği üzerine de çalışılacaktır. Bunun için ise, kullanılacak organik yarıiletkenler, örneğin CSA ile katkılandırarak güneş hücresinin verimliliği arttırılmaya çalışılacaktır.  Daha önce yapılan literatür taramalarında bu tür bir katkılandırmanın etkisi üzerine bir çalışma bulunamamıştır. Bu sebepten dolayı yapacağımız bu çalışma öncü bir adım olacaktır ve özgünlüğünü buradan almaktadır. Polimer güneş hücrelerinde, soğrulmayı sağlayan malzeme organik malzemelerdir. Örneğin “conjugated” polimer gibi. Bu güneş hücrelerinin temel çalışma prensibi diğer formdaki güneş hücreleriyle benzerdir çünkü elektromanyetik dalga formundaki enerjinin, elektrik enerjisine dönüştürülmesidir. Bu fiziksel olaya fotovoltaik etki denir. Bu enerji çevrimini, yarıiletkenler kullanarak yapmak mümkündür. Silisyum tabanlı güneş hücreleri için pahalı vakum teknikleri kullanılmaktadır fakat polimer güneş hücreleri, çok basit ve ucuz bir şekilde hazırlanan solüsyonlardan elde edilebilmektedir. Bu yöntemle, esnek yapıda, üretimi kolay, düşük maliyetli güneş hücreleri elde etmek mümkündür. Güneş hücrelerinin verimini olumsuz etkileyen başlıca parametreler şunlardır; gelen ışığın yetersiz absorpsiyonu, hücre içindeki tabakalar arası direncin büyüklüğü, oluşan elektron-deşik çiftlerinin tekrar birleşmeden elektrotlara gidebilmeleri için mobilitelerinin yeterli olmamasıdır.  Son olarak, bu tez çalışmasında, organik güneş hücrelerini oluşturan temel unsur olan organik yarıiletkenlerin elektiriksel ve spektroskopik özelliklerinin incelemesi ve çeşitli yöntemlerle, bu güneş hücrelerinin verimliliğini olumsuz etkileyen faktörlerin ortadan kaldırılmaya çalışılmasıdır.

There has been a great interest on conducting polymers since the discovery of a polymer which can conduct electricity. These polymers can be used in many applications such as organic light emitting diodes, organic solar cells, transparent optical coatings and other optoelectronic devices etc. Polymer solar cells (PSCs) have been promising alternative instead of silicon based solar cells because of their advantages in terms of low cost, light weight and flexibility. Poly(3-hexylthiophene) (P3HT) is the most used material in active layer for bulk-heterojunction (BHJ) and organic solar cells due to semiconducting properties. But the efficiencies of these solar cells are still low. The reason is that charge carrier mobilities are low and  owing to this molecular excitonic nature of the primary excitation, absorption spectrum of organic conjugated polymers are restricted to a few 100 nm width instead of to absorption spectra  compared to inorganic materials. Because of these reasons, to understand the nanostructure of the doped P3HT nanofilms are crucial for improving and designing optimum device architecture.  P3HT is air stable conducting polymer and has attracted so much attention on account of high electrical conductivity. Orbital energies of P3HT are - 5.1 eV for HOMO (highest occupied molecular orbital) and -2.9 eV for LUMO(lowest unoccupied molecular orbital). In addition, self-organization of P3HT are very important  and it can be influenced by its degree of regioregularity characterized as the percentage of monomers related between “head to tail” (HT) coupled monomers. The effect of doping a polymer with Camphor Sulfonic Acid (CSA) has been successfully demonstrated and has been exhibited to produce nanofilms of high conductivity with a decreased temperature dependence. Therefore, in this study, to the best of our knowledge no study was reported in the available literature concerning investigation on the effect of CSA doping on structural, spectroscopically and electrical transport properties of P3HT nanofilms.  We aimed to understand the morphological, spectroscopic and electrical properties of pristine P3HT thin films and doped film with CSA to obtain more efficient BHJ solar cell. In this purpose, we tried to increase the absorption and conductivity of P3HT nanofilms doping with CSA. Also we changed the annealing temperatures during the experiment to investigate how the annealing process affects the film properties, such as conductivity and optical properties of these pristine and doped P3HT nanofilms. Poly(3-hexylthiophene) (P3HT) and Camphorsulfonic acid (CSA) were used as semiconductor polymer and dopant molecule, respectively. They were dissolved in. p-xylene, 5mg/mL of P3HT kept fix for preparing each solution. Glass substrates are used for preparing pristine and doped P3HT thin films. The solution is heated up to the 80 °C and stirred for 1.5 hour. Thin films were prepared by wire bar coater, Glass substrates were waited on the hot plate of wire bar coater to heat them to 40°C and 70°C to prepare two thin films having different morphology. After coated the substrates with polymer solution, the films were held on the hot plate for 2 minutes until evaporating the solution from the substrate. The same procedure was carried out for preparing doped P3HT nanofilms, but, differently, 10mg CSA was added the solution at the same time with P3HT. Then the glass substrates were coated at different annealing temperature for doped P3HT thin films. The prepared CSA-doped and pristine P3HT nanofilms were examined by various techniques. The morphologies of the prepared nanofilms were examined by atomic force microscopy (AFM; AFM, SPM-9500 J3, Shimadzu). To investigate the optical properties, the prepared nanofilms were investigated by UV. Vis. Spectroscopy (Lambda 35) and fluorescence spectroscopy (Varian Cary Eclipse). The thickness of the prepared nanofilms were studied by DEKTAK, The electrical properties of the prepared films were inspected by Keithley Model 6487 Picoammeter/Voltage Source. Transmittance and reflectance spectra of the films were measured in the spectral range between 390 and 1000 nm in s polarization at 30° angle of incidence by an NKD-7000 V (Aquila Instruments, England) model spectrophotometer.  As known from literature, absorption of pristine P3HT films highly depends on the film processing conditions such as solvent properties and annealing procedures. Also, morphology of films affects electronic structure and thus spectroscopic responses. Pristine and doped P3HT films prepared at 40°C show one broad peak, the maxima of these peaks take place at 520 nm and 535 nm, respectively. Eventually, P3HT generally shows one broad absorption peak when it dissolve in a solution. AFM images of pristine and doped films prepared at 40°C and 70°C show that . The root mean square (RMS) surface roughness values of the pristine films were found as 1.7 nm and 1.3 nm for the films prepared at 40°C and 70°C, respectively. On the other side, the RMS values of the doped films were found as 3.3nm and 7.1 nm for the films prepared at 40°C and 70°C, respectively. The AFM images show that there are tiny and dense hills on the surface of the pristine films. Also, it can be clearly seen on the AFM results, RMS values and grain size increase with the doped CSA and surface of the doped films have more rough structure. Hence, in the both films, aggregation of CSA molecules are seen in doped films. Moreover, as seen in the AFM image, the hills (grains) coalesce and get higher for the doped films prepared at 70°C. This shows that the agglomeration tendency of CSA molecules increase with the increase of annealing temperature. Therefore, CSA is not seen to incorporate in the polymer matrix when the films prepared at 70°C. This results is consistent to UV and fluorescence measurements which they show the doping effect is more pronounced for the samples prepared at 40°C. Conductivity of the samples at the room temperature is increased nearly 3 fold by doping We achieved that the conductivity of the P3HT nanofilms increased when the films are doped with CSA such as the conductivity increased from 5,89 ×〖10〗^(-5) S/cm to 1,39 ×〖10〗^(-4)  S/cm for 40°C preparation temperature. After the understanding of  doping effect on P3HT organic semiconductor. We tried to make organic solar cells by using doped P3HT. These solar cells which include P3HT:PCBM, CSA and Poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonate) (PEDOT:PSS). Also, [6,6]-Phenyl C61 butyric acid methyl ester (PCBM) is used as acceptor material and PEDOT:PSS is used as hole transport layer in solar cell. We made two solutions. One of them included just P3HT:PCBM   and the other one included P3HT:PCBM:CSA so that we tried to increase the efficiency of the solar cell using by CSA. Then we formed the solar cells with spin coating. By the way, we utilized p-Xylen to solve the donor and acceptor material at the same solution. One of the obstacles during the experiment was that we couldnt coat PEDOT:PSS smoothly. Because of this reason, we tried to reduce the density of PEDOT:PSS. In this purpose, we mixed the PEDOT:PSS with pure water. Then We coated PEDOT:PSS on indium tin oxide (ITO) coated glass substrate. After that, we coated the our organic semiconductor solution on PEDOT:PSS and then finally we put the top electrode  which is Aluminium (Al), it was dot contact. Also Al was coated in ultra high vacuum. This description is for normal geometry. Besides, we made the solar cell which had inverted geometry. It means that we coated our organic semiconductors first then we coated the hole transport layer which was PEDOT:PSS. Actually, using different geormetries, we just changed the anode and cathode position in organic solar cell. In other words, we changed the direction of electrons and holes in our organic solar cell. Thus, we investigated absorption, flourescene and efficiency of our solar cells. The absorption and flourescene spectrum of the organic solar cells were like other studies in literature but when we put our solar cells to solar simulator, The I-V curve of the solar cells were like diode. We didnt see any photovoltaic effect on the device. We used another organic semiconductor which was Poly[2,6-(4,4-bis-(2-ethylhexyl)-4H-cyclopenta[2,1-b;3,4-b′]dithiophene)-alt-4,7(2,1,3-benzothiadiazole)] (PCPDTBT)  We prepared solutions. the solvent that was Tetrahydrofuran (THF) for PCPDTBT. We doped PCPDTBT with CSA and Dodecylbenzenesulfonic acid (DBSA) So we prepared three different solutions which are pristine PCPDTBT, doped with CSA and DBSA. Then we coated the glass substrates with prepared solutions. Then we investigate the absoprtion and flourescene spectrum of the thin films. We didnt see remakable change in the absorption spectra of CSA doped thin films. But  when we investigated the thin films which were coated with DBSA, there is a rise at the infrared region. It means that the doping with DBSA can increase the efficiency of the solar cells. Finally, we made the organic solar cells with PCPDTBT. Again we used ITO coated substrates. Also, we prepared the solar cells with CSA and with different geometries. We prepared solutions which were made of PCPDTBT:PCBM and PCPDTBT:PCBM:CSA. But we didnt see any photovoltaic effect in these organic solar cells using by solar simulator. They behaved just like a normal diode.
The Electrical And Spectroscopic Properties Of The Prepared Semiconductor Thin Films Of Polymers and Organic Solar Cells
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2016
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2016
Keywords: Polimer Yarıiletkenler; Organik Güneş Hücreleri; Polymer Semiconductors; Organic Solar Cells